Avaliação externa na educação de jovens e adultos: análises e perspectivas - Miranda, Juliana (2013)
The Youngster and Adult Education (YAE) faces major challenges related to contemporary social and economic needs. If this system once has had the stigma that was enough to teach adults and adolescents who dropped out or never went to school to read and write his name, today YAE has the challenge of providing a broad and inclusive education that enables its students to not only be part of the labor market, but also to worthy and effective a social inclusion. Due to these new goals sought by YAE, the pedagogical and management planning of this teaching modality need to be aligned with contemporary social, cultural and economic conditions. Therefore, the large-scale assessments done to diagnose the skills and competencies of students and offer portraits of the macro institutional activity, may appear as valuable tools for the development of actions and interventional projects aimed at the adequacy of management and pedagogical actions to improve the quality of education for the students and the performance of the educational systems. In this scenario, this study is meant to perform the analysis of an evaluation project on Youngster and Adult Education program as a way to demonstrate the importance of conducting an external assessment also to this type of teaching modality